2018
DOI: 10.7146/tfss.v15i28.107261
|View full text |Cite
|
Sign up to set email alerts
|

Et udstrakt selv

Abstract: Artiklen undersøger unge studerendes (18-25 år) narrativer om trivsel og håndtering af præstationskrav i forbindelse med at være under uddannelse. Unges brug af receptpligtig medicin til ikke-medicinske formål som at trives eller præstere bedre diskuteres i lyset af et øgende præstations- og effektivitetspres i det danske uddannelsessystem. Analysen viser, at de unge bruger medicin ud fra meget forskellige logikker og forbehold. Nogle unge normaliserer egen brug og ser den som en legitim måde at håndtere oplev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Furthermore, counselors are concerned about the increase in diagnoses among young people in general, as well as about indications that more students than before use performance-enhancing drugs. Finally, they are concerned about the pressure that is born of the requirement to present oneself as a successful being on social media [39]. The counselors reflect on how recent structural developments also cause new requirements for their daily work with the students.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, counselors are concerned about the increase in diagnoses among young people in general, as well as about indications that more students than before use performance-enhancing drugs. Finally, they are concerned about the pressure that is born of the requirement to present oneself as a successful being on social media [39]. The counselors reflect on how recent structural developments also cause new requirements for their daily work with the students.…”
Section: Resultsmentioning
confidence: 99%
“…We have until now described recent changes from the perspective of educational counselors, but the tendencies described above are also central in our interviews with students as described elsewhere [12,18,39]. In the next section, we discuss how the counselors understand some of the different coping strategies used by students.…”
Section: Social Mediamentioning
confidence: 97%
See 1 more Smart Citation
“…During these times, a sense of urgency or 'crisis' can provoke a shift in personal ethics where drug use is considered more of a necessity than a choice as a mechanism of managing performance and achievement. Thus, a sense of ambivalence is often embedded in narratives around PCED use (Bjønness, 2018;Krøll, 2019, this issue;Loe & Cuttino, 2008).…”
Section: Moralising Justifying and (De)legitimating Pcementioning
confidence: 99%
“…However, and as several scholars assert, this prohibitory stance and identity of these substances as prescribed or controlled medicines does not appear to be putting everyone off using them as PCEDs, (see for example, Bjønness, 2019;Petersen & Petersen, 2019, both this issue). Furthermore, studies have found that some PCED users regard the medicinal status of PCEDs as a symbol of their safety despite their consumption practices falling outside of medically sanctioned uses (Bjønness, 2018).…”
Section: Regulating Pcedsmentioning
confidence: 99%